Cloning of tomato (Lycopersicon esculentum Mill.) arginine decarboxylase gene and its expression during fruit ripening. - Rastogi, R (1993)
Arginine decarboxylase (ADC) is the first enzyme in one of the two pathways of putrescine biosynthesis in plants. The genes encoding ADC have previously been cloned from oat and Escherichia coli. Degenerate oligonucleotides corresponding to two conserved regions of ADC were used as primers in polymerase chain reaction amplification of tomato (Lycopersicon esculentum Mill.) genomic DNA, and a 1.05-kb fragment was obtained. This genomic DNA fragment encodes an open reading frame of 350 amino acids showing about 50% identity with the oat ADC protein. Using this fragment as a probe, we isolated several partial ADC cDNA clones from a tomato pericarp cDNA library. The 5' end of the coding region was subsequently obtained from a genomic clone containing the entire ADC gene. The tomato ADC gene contains an open reading frame encoding a polypeptide of 502 amino acids and a predicted molecular mass of about 55 kD. The predicted amino acid sequence exhibits 47 and 38% identify with oat and E. coli ADCs, respectively. Gel blot hybridization experiments show that, in tomato, ADC is encoded by a single gene and is expressed as a transcript of approximately 2.2 kb in the fruit pericarp and leaf tissues. During fruit ripening the amount of ADC transcript appeared to peak at the breaker stage. No significant differences were seen when steady-state ADC mRNA levels were compared between normal versus long-keeping Alcobaca (alc) fruit, although alc fruit contain elevated putrescine levels and ADC activity at the ripe stage. The lack of correlation between ADC activity and steady-state mRNA levels in alc fruit suggests a translational and/or posttranslational regulation of ADC gene expression during tomato fruit ripening.